Evaluation and Improvement of Chocolate Bar Production at CV. XYZ Factory - Larasati, Widya; Rahayu, Wahidah Mahanani; Nurrohmah, Beta Achromi (Journal of Agri-Food Science and Technology, 2022)
CV. XYZ is a chocolate bar industry in Yogyakarta. The Village community carries out the industry. It creates cocoa product innovation from upstream to downstream products. This research contributes to evaluating the chocolate tempering to determine the fat content of the chocolate bar obtained. The proper tempering techniques and defect evaluation are conducted to determine the reasons for defects in chocolate bars. Good chocolate characteristics consist of the chocolate bar, such as being quickly released from the cast/not sticky, obtaining a glossy/glossy surface on the chocolate bar, being hard and crunchy when broken, and being resistant to melt at room temperature. The standard for the tempering process is set by CV. XYZ produces chocolate bars from the tempering process to produce chocolate bars with shiny/glossy look and crunchy.